Cardiac tamponade secondary to hemorrhagic pericardial effiision in five dogs - HATZIGIANNAKIS (Χ.Γ. ΧΑΤΖΗΓΙΑΝΝΑΚΗΣ), C. G.; MYLONAKIS (Μ. Ε. ΜΥΛΩΝΑΚΗΣ), M. E.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N.; PATSIKAS (Μ. ΠΑΤΣΙΚΑΣ), M.; PSALLA (Δ. ΨΑΛΛΑ), D.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A 7-year old female collie (case 1), a 3-year old male Caucasian-cross (case 2) and three male German shepherds with an age of 11 (case 3), 8.5 (case 4) and 10 (case 5) years, respectively, were admitted with a history of decreased appetite, depression, exercise intolerance, dyspnea and progressive abdominal enlargement, for the last 10 to 60 days. Poor body condition (5/5), muffled heart sounds (5/5), weak femoral pulse (5/5), ascites (5/5), inspiratory or inspiratory-expiratory dyspnea (5/5), pulsus paradoxus (2/5) and jugular vein distension (2/5) were the prominent clinical findings, while mature neutrophilic leukocytosis (3/5), lymphopenia (3/5), eosinopenia (3/5), hypoproteinemia (5/5) and increased urea nitrogen (3/5) were the most prevalent clinicopathologic abnormalities. Apart from a space-occupying lesion onto the right atrial wall of one dog (case 4), radiographic and ultrasound examination showed a globe-shaped cardiac silhouette (5/5), pericardial effusion (5/5), ascites (5/5) and pleural effusion (4/5). A large amount of non-clotting hemorrhagic effusion was drained during pericardiocentesis, resulting in rapid clinical recovery. Physical, chemical and cytological evaluation of the pericardial fluid was non-contributory in the differentiation between neoplastic and non-neoplastic causes of these effusions. Case 3 died 25 days post-pericardiocentesis; right atrium hemangiosarcoma and pulmonary metastases were documented on post mortem histopathological examination. Another dog (case 5) died of unknown causes one month after pericardiocentensis. On the contrary, dogs 1, 2 and 4 were still clinically healthy for a followup period of 16, 2 and 8 months, respectively.